Mengkaji Kitab Bulugh al-Maram - Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2018)
This paper discusses the study of the book of Bulugh al-Maram by Imam Ibn Hajar al-Asqalany. This is important, because the book is very popular studied in boarding school. But many of us who do not know about the ins and outs of the book. This study is included in the literature research. The method used by the authors in this study is the method of description that is referring to the books or related references and then pour and summarize in this paper. As for the result of this discussion is the book of Bulugh al-Maram belongs to the classification of the book of law. As for the underlying factors in the compilation of this book is the dissolution of scientific scholars of the scholars to various regions of Islam and the attention of people who tend to greater to study the problems of furu'(branch). Keywords: bulugh al-maram, hadith, sharh